How neurons migrate: a dynamic in-silico model of neuronal migration in the developing cortex - Setty, Yaki; Chen, Chih-Chun; Secrier, Maria; Skoblov, Nikita; Kalamatianos, Dimitrios; Emmott, Stephen (BMC Systems Biology, 2011)
Neuronal migration, the process by which neurons migrate from their place of origin to their final position in the brain, is a central process for normal brain development and function. Advances in experimental techniques have revealed much about many of the molecular components involved in this process. Notwithstanding these advances, how the molecular machinery works together to govern the migration process has yet to be fully understood. Here we present a computational model of neuronal migration, in which four key molecular entities, Lis1, DCX, Reelin and GABA, form a molecular program that mediates the migration process.